Research Advances on Fiber-Optic SPR Sensors with Temperature Self-Compensation - Zhao, Hongxia; Wang, Feng; Han, Zhaojia; Cheng, Peihong; Ding, Zhiqun (Sensors (Basel, Switzerland), 2023)
The fiber-optic surface plasmon resonance sensor has very promising applications in environmental monitoring, biochemical sensing, and medical diagnosis, due to the superiority of high sensitivity and novel label-free microstructure. However, the influence of ambient temperature is inevitable in practical sensing applications, and even the higher the sensitivity, the greater the influence. Therefore, how to eliminate temperature interference in the sensing process has become one of the hot issues of this research field in recent years, and some accomplishments have been achieved. This paper mainly reviews the research results on temperature self-compensating fiber-optic surface plasmon sensors. Firstly, it introduces the mechanism of a temperature self-compensating fiber-optic surface plasmon resonance sensor. Then, the latest development of temperature self-compensated sensor is reviewed from the perspective of various fiber-optic sensing structures. Finally, this paper discusses the most recent applications and development prospects of temperature self-compensated fiber-optic surface plasmon resonance sensors.